Daygurt: A functional drink combining dadih and yoghurt from cow’s milk using response surface methodology - Gusnedi; Ahmad Habibi Nur; Sartika Wiwi; Darwel; Tristi Utami Citra (BIO Web of Conferences)
Response Surface Methodology (RSM) was employed to optimize the formulation of Daygurt, a functional drink combining dadih and yogurt made from cow's milk. The independent variables included the percentages of dadih, yogurt, and skimmed milk, while the optimized responses encompassed sensory profile, viscosity, pH, and protein content. Statistical analysis revealed significant effects of the variables on aroma and texture. The optimal formulation was determined to consist of 1% dadih, 4.89% yogurt, and 9.1% skimmed milk. The experimental values closely aligned with the predicted values, showing a 95% Confidence Interval (CI), confirming the model's accuracy. Quality and safety assessment confirmed that Daygurt complied with the standards established by the Indonesian Food and Drug Authority.